Anesthesia methods for full-endoscopic lumbar discectomy: a review - Zheng, Bin; Guo, Chen; Xu, Shuai; Li, Haoyuan; Wu, Yonghao; Liu, Haiying (Frontiers in Medicine, 2023)
Full-endoscopic lumbar discectomy under local anesthesia is major trends for the treatment of lumbar disc herniation in spine minimally invasive surgery. However, sometimes local anesthesia is not enough for analgesic in surgery especially in interlaminar approach. This study summarizes the current study of anesthesia methods in full-endoscopic lumbar discectomy. Local anesthesia is still the most common anesthesia method in full-endoscopic lumbar discectomy and the comparison group for other anesthesia methods due to high safety. Compared to local anesthesia, Epidural anesthesia is less applied in full-endoscopic lumbar discectomy but reports better intraoperative pain control and equivalent safety due to the motor preservation and pain block characteristic of ropivacaine. General anesthesia can achieve totally pain block during surgery but nerve injury can not be ignored , and intraoperative neuromonitoring can assist. Regional anesthesia application is rare but also reports better anesthesia effects during surgery and equivalent safety. Anesthesia methods for full-endoscopic lumbar discectomy should be based on patient factors, surgical factors, and anesthesiologist factors to achieve satisfactory anesthesia experience and successful surgery.